Influence of tyrosine kinase inhibitors and everolimus on TGFβ1 and TGF-β receptor 2 in squamous cell carcinoma cells - Huber, Lena; Knüttel, Manuel Thomas; Kramer, Benedikt; Zaubitzer, Lena; Lammert, Anne; Scherl, Claudia; Rotter, Nicole; Häussler, Daniel (Anticancer research, 2024)
Background/Aim: Transforming growth factor-β (TGF-β) plays a significant role in the formation of different cancer subtypes. There is evidence that TGF-β pathways promote cancerogenic cell characteristics but also have tumor-suppressor capabilities. The tyrosine kinase inhibitors nilotinib, dasatinib, erlotinib, gefitinib, and everolimus are approved as targeted therapies for several tumor entities, including head and neck squamous cell carcinoma (HNSCC). This study aimed to investigate the effects of these substances on the expression levels of TGFβ1 and TGF-β receptor type 2 (TGFβR2) in HPV-negative and HPV-positive SCC cell cultures. Materials and Methods: Expression patterns of TGFβ1 and TGFβR2 were determined using enzyme-linked immunosorbent assay (ELISA) in three HNSCC cell lines (i.e., HNSCC-11A, HNSCC-14C, and CERV196). These cells were incubated with nilotinib, dasatinib, erlotinib, gefitinib, and everolimus (20 μmol/l) and compared to a chemonaive control. An assessment of concentration levels was conducted after 24, 48, 72, and 96 h of treatment. Results: Statistically significant changes in the expression levels of TGFβ1 and TGFβR2 were found in all tested cell cultures (p<0.05) compared to the negative control. An increase in TGFβ-R2 expression was detected after treatment with most of the tested tyrosine kinase inhibitors, whereas a reduction in TGFβ1 was observed. The addition of everolimus had the opposite effect on both TGFβR2 and TGF-B1- expression. Conclusion: Expression of TGFβ1 and TGFβR2 was detected in all cultured HNSCC cell lines. Nilotinib, dasatinib, erlotinib, gefitinib, and everolimus had an impact on the expression levels of TGFβ1 and TGFβR2 in vitro.
Online veröffentlicht: 26. Juli 2024
Gesehen am 25.02.2025